2013
DOI: 10.1371/journal.pone.0056250
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adiponectin Levels Correlate Positively with an Increasing Number of Components of Frailty in Male Elders

Abstract: ObjectiveFrailty is an important geriatric syndrome. Adiponectin is an important adipokine that regulates energy homeostasis. The aim of this study is to investigate the relationship between plasma adiponectin levels and frailty in elders.MethodsThe demographic data, body weight, metabolic and inflammatory parameters, including plasma glucose, total cholesterol, triglyceride, tumor necrosis factor alpha (TNF-α), c-reactive protein (CRP) and adiponectin levels, were assessed. The frailty score was assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 38 publications
3
42
3
Order By: Relevance
“…Although thus far there have been few data investigating the relationship between adiponectin and frailty, one study in which 168 elderly participants (aged 76.9 years) were investigated showed that high plasma adiponectin levels were associated with frailty in older adults, and were positively correlated with an increasing number of components of frailty in older men . There are two differences in the characteristics of the study participants between that study and the present.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Although thus far there have been few data investigating the relationship between adiponectin and frailty, one study in which 168 elderly participants (aged 76.9 years) were investigated showed that high plasma adiponectin levels were associated with frailty in older adults, and were positively correlated with an increasing number of components of frailty in older men . There are two differences in the characteristics of the study participants between that study and the present.…”
Section: Discussioncontrasting
confidence: 54%
“…Although age‐related hormonal changes, such as growth hormone, sex hormones and vitamin D, play important roles in the exacerbation of frailty and sarcopenia, there are few other studies that have referred to the relationship between frailty and adiponectin . It was reported that plasma adiponectin levels were positively correlated with an increasing number of frailty components in older men . In their study, frail patients were significantly older than non‐frail patients, whereas the ages of frail and non‐frail participants in the present study were almost the same: approximately 83 years.…”
Section: Introductioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Aging is a deleterious, progressive, intrinsic and universal process that affects functional, physiological, biological and social changes over time . Relevant features of age are metabolic syndrome, sarcopenia, frailty, loss of functionality and inflammation . Prolonged inflammation has harmful health effects and predisposes individuals to a variety of chronic diseases, and it is a strong predictor of disability and mortality …”
Section: Introductionmentioning
confidence: 99%